Interrelasi Kualitas Website dengan Keputusan Pembelian dan Fungsi Pemediasi Brand Ambassador - Arliansyah, Rafli; Sugito, Pudjo (Business Management Research, 2022)
The dynamics of the development of e-commerce in Indonesia is supported by the rapid development of information technology in the form of the internet. The existence of e-commerce makes it easier for shopping activities that are not limited by place and time. e-commerce requires a place called a website which then the website can be measured using Webqual 4.0. Not only relying on web quality alone, the role of brand ambassadors is also needed in attracting consumers and influencing their purchasing decisions. This study aims to analyze the direct influence of website quality on purchasing decisions, the role of brand ambassadors on website quality on purchasing decisions, and the direct influence of brand ambassadors on purchasing decisions on Shopee customers in Malang City. This type of research is a quantitative research, with an unknown population of Malang City, while the sample in this study was 100 respondents. The sampling technique in this study used accidental random sampling. Data collection is done online using a google form containing a questionnaire, which is then distributed through private chats and group chats. Analysis of the data used is the Structure Equation Model (SEM) using Smart PLS 3. The results show that website quality has a direct effect on purchasing decisions, website quality affects brand ambassadors on purchasing decisions, and brand ambassadors directly affect purchasing decisions.